Long-term Apomorphine Infusion Users Versus Short-term Users: An International Dual-center Analysis of the Reasons for Discontinuing Therapy. Issue 5 (September 2019) - Bhidayasiri, Roongroj; Phokaewvarangkul, Onanong; Boonpang, Kamolwan; Boonmongkol, Thanatat; Thongchuem, Yuwadee; Kantachadvanich, Nitinan; García Ruiz, Pedro J.
Abstract : Objectives: A retrospective analysis at 2 specialist centers was undertaken to determine the long-term efficacy of subcutaneous apomorphine infusion (APO), rates and reasons for discontinuation, and factors that might contribute to discontinuation. Methods: Demographics, clinical outcomes data, and reasons for discontinuation were collected for patients treated with APO at Chulalongkorn Centre of Excellence for Parkinson's Disease and Related Disorders, Bangkok, Thailand (n = 36) and Fundacion Jimemez Diaz Universidad Autonoma de Madrid, Spain (n = 16). Results: There were 19 (52.7%) patients in the Thai cohort and 10 (62.5%) patients in the Spanish cohort who discontinued treatment within around 6 months of initiation, most commonly due to skin nodules (Thai cohort) and perceived lack of efficacy (Spanish cohort). Those who continued APO tended to stay on treatment. In both cohorts, APO resulted in significant reductions in Unified Parkinson's Disease Rating Scale 3 motor scores, daily OFF time, and levodopa-equivalent dose in patients who subsequently stopped therapy, suggesting APO is clinically effective even when "lack of efficacy" is stated as a reason for discontinuing. Daily OFF hours after APO therapy was found to be a significant predictive factor for APO discontinuation with an odds ratio of 5.952 ( P = 0.040). The cutoff point that determined APO discontinuation was calculated to be 1.75 or more OFF hours (sensitivity, 84.6%; specificity, 63.2%). Conclusions: Apomorphine infusion is a minimally invasive therapy and therefore very easy to discontinue if difficulties arise. This fact might explain the high dropout rate of this technique. Successful long-term adherence to APO therapy requires a multidisciplinary health care team approach including regular patient follow-up and assessment and prompt resolution of queries and concerns. Abstract : Supplemental digital content is available in the text.